2010
DOI: 10.3389/neuro.05.008.2010
|View full text |Cite
|
Sign up to set email alerts
|

Retinal afferents synapse with relay cells targeting the middle temporal area in the pulvinar and lateral geniculate nuclei

Abstract: Considerable debate continues regarding thalamic inputs to the middle temporal area (MT) of the visual cortex that bypass the primary visual cortex (V1) and the role they might have in the residual visual capability following a lesion of V1. Two specific retinothalamic projections to area MT have been speculated to relay through the medial portion of the inferior pulvinar nucleus (PIm) and the koniocellular layers of the dorsal lateral geniculate nucleus (LGN). Although a number of studies have demonstrated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 95 publications
7
120
0
Order By: Relevance
“…Previous studies have demonstrated the presence of two monosynaptic pathways from the pulvinar nucleus and LGN to area MT in adult nonhuman primates (Lin and Kaas, 1980;Cowey et al, 1994;Adams et al, 2000;O'Brien et al, 2001;Warner et al, 2010), but none have examined when they are present and whether they change during development. Therefore, injection of the retrograde tracer FB into area MT (Fig.…”
Section: Area Mt Is Recipient Of Direct Input From the Pim Lgn And V1mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the presence of two monosynaptic pathways from the pulvinar nucleus and LGN to area MT in adult nonhuman primates (Lin and Kaas, 1980;Cowey et al, 1994;Adams et al, 2000;O'Brien et al, 2001;Warner et al, 2010), but none have examined when they are present and whether they change during development. Therefore, injection of the retrograde tracer FB into area MT (Fig.…”
Section: Area Mt Is Recipient Of Direct Input From the Pim Lgn And V1mentioning
confidence: 99%
“…The previously described retinofugal pathways to area MT via the koniocellular (K) layer of the lateral geniculate nucleus (LGN) (Sincich et al, 2004) and medial portion of the inferior pulvinar nucleus (PIm) (Sincich et al, 2004;Lyon et al, 2010;Warner et al, 2010) are likely candidates (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…1) (Felleman & Van Essen, 1991). The innervation of the visual cortex by the thalamus is also highly segregated in the primates, with the lateral geniculate nucleus (LGN) specifically innervating V1, and the other visual thalamic nuclei such as the pulvinar innervating extrastriate areas such as the MT area (Sincich et al 2004;Lyon et al 2010;Warner et al 2010). The discovery and analysis of visual cortical areas in the human and non-human primates have been a major accomplishment in visual neuroscience, and the location, number and functional roles of the individual nuclei are major topics of investigation in the adult and developing brain.…”
Section: Parcellation and Connectivity Of The Visual Cortexmentioning
confidence: 99%
“…Furthermore, this has been recently enhanced with an increased number of fluorescent-conjugated tracers (e.g. B-subunit cholera toxin) (Warner et al 2010;Angelucci et al 1996;Behrens et al 2003), and complex transneuronal tracers including the neurotropic (rabies) viruses used by Edward Callaway and colleagues in macaque monkeys , 2007, which can be produced to cross a predetermined number of synapses in the visual system. Although tracer studies are limited primarily to studies in experimental animals, new techniques in magnetic resonance imaging (MRI) such as diffusion tensor imaging (which measures the restrictions on water along nerve fibre bundles) has shown potential in enabling the mapping of thalamocortical and corticocortical connectivity (Behrens et al 2003;Hagmann et al 2003;Dauguet et al 2007;Bridge et al 2008), and although there are specific limitations with this technique, it has become an invaluable resource for studying both the intact and damaged human brain.…”
Section: Parcellation and Connectivity Of The Visual Cortexmentioning
confidence: 99%
See 1 more Smart Citation